The Influence Of Social Media Marketing On Destination Image And Intention To Visit Tourist Destinations (Study On Belitar Seberang Tourism Village) - Widarmanti, Tri; Nugraha, Muhammad Rakha (UNIVERSITAS PAKUAN, 2019)
Technological developments have changed society; this is in line with the presence of social media, which offers broad benefits and potential. This study aims to test and analyze how social media marketing influences destination image, how social media marketing influences visit intentions, how destination image influences visit intentions, and how social media marketing influences visit intentions mediated by destination image. Data was collected through an online questionnaire, and the population in this study, namely followers from the official Instagram account of the Belitar Seberang Tourism Village, a total of 155 valid questionnaires were obtained and analyzed using partial least squares structural equation modeling (PLS-SEM) with WarpPLS 7.0 software. The findings positively support the direct effect of social media marketing on destination image and visit intentions. In addition, the results of this study confirm the positive influence of the mediating role of destination image on social media marketing and the intention to visit. This study offers views on the role of social media marketing in increasing the intention to visit tourist destinations, either directly or through the image of the destination.